PENGAWASAN PEREDARAN PRODUK PANGAN (MAKANAN KALENG) OLEH BALAI BESAR PENGAWAS OBATDAN MAKANAN (BBPOM) DI KOTA PEKANBARU - Ayu Mulyani Noor; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Circulation of canned food products that are not suitable with the applicable provisions is still a problem for the city of Pekanbaru. This study was conducted to determine Monitoring that do carried out by Balai Besar Pengawas Obat and Makanan on the circulation of canned food products in Pekanbaru. By looking at surveillance BBPOM Pekanbaru to distribution facilities that sell canned food products in Pekanbaru.Research conducted using qualitative method with kind of descriptive research. This study used a control theory Manullang with standard assign, conducting evaluate and conducting corrective action. In this study conducted technique is observation, interviews and documentation by using the technique of analysis.These results indicate that controlling of food products (canned food) by BBPOM in Pekanbaru is still not going well due to the lack of guidance to enterpreneur and public, the legal sanctions are not yet firmly, still inadequate number of employees and number of operational vehicles, as well as the lack of public participation in monitoring the circulation of canned food products in Pekanbaru. Therefore, in order to optimize controlling of food products (canned food) by BBPOM in Pekanbaru is necessary to improve guidance to enterpreneur and public, providing legal sanctions firmly, and increasing the number of employees and operational vehicles BBPOM Pekanbaru.Keywords: Control, Distribution Facilities, BBPOM